PENGARUH TERAPI AKTIVITAS KELOMPOK HARGA DIRI TERHADAP PENINGKATAN HARGA DIRI PASIEN DENGAN HARGA DIRI RENDAH DI PANTI SOSIAL TRESNA WERDHA BUDI MULIA I CIRACAS JAKARTA TIMUR - Nurul Fatma; Hernida Dwi Lestari; Didi Sutisna (Afiat, 2019)
Introduction group activity therapy is one of the modality therapies performed by nurses to a group of clients. The group activity therapy is used as therapy, and the group is used as the target of care. Management of clients with low self-esteem can be done one of them by providing a stimulus or stimulation that triggers a positive perception of himself. The purpose of this study was to determine the effect of low self-esteem group activity therapy on increasing self-esteem of patients with low self-esteem at Sasana Tresna Werdha 3 Ciracas, East Jakarta. The research method is quantitative with a type of quasi experiment research with pre and post test design. The research sample of 15 respondents through purpose sampling techniques. The results of the analysis study obtained the value of client self-esteem before therapy of group activity with an average of 14.60 with a standard deviation of 0.828. While self-esteem after group activity therapy, an average of self-esteem is 16.27 with a standard deviation of 0.458, then the P- value value (0,000) where the value (P-value <0.05. The conclusion that the provision of group activity therapy influences self-esteem to clients at Tresna Werdha Budi Mulia Social Home 1 Ciracas, East Jakarta. Suggestions It is expected that nurses can provide training on how to socialize and teach clients the ability to increase self-esteem in clients.